2022
DOI: 10.3389/fnmol.2022.967103
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural and functional changes during menstrual migraine: Relationships with pain

Abstract: ObjectivesMenstrual migraine (MM) is a special type of migraine associated with the ovarian cycle, which imposes a marked burden on female patients. However, the pathogenesis of MM is not completely understood. We investigated gray matter volume (GMV) and functional connectivity (FC) alterations in patients with MM to explore whether there are changes in resting-state FC (rsFC) in brain regions with structural GMV abnormalities and investigated their relevance to pain and concomitant symptoms.MethodsSeventy-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…It may be involved in analgesic effects, and its stimulation may lead to impaired judgment of pain intensity and reduce perceived pain intensity ( 47 ). The altered function and structure of the superior parietal gyrus has also been found in other pain disorders ( 48 - 50 ). Therefore, the hypoconnectivity between the PAG and the superior parietal gyrus in this study may suggest the disorder of the descending pain modulation system.…”
Section: Discussionmentioning
confidence: 81%
“…It may be involved in analgesic effects, and its stimulation may lead to impaired judgment of pain intensity and reduce perceived pain intensity ( 47 ). The altered function and structure of the superior parietal gyrus has also been found in other pain disorders ( 48 - 50 ). Therefore, the hypoconnectivity between the PAG and the superior parietal gyrus in this study may suggest the disorder of the descending pain modulation system.…”
Section: Discussionmentioning
confidence: 81%
“…Recent brain fMRI studies supported the existence of functional differences between women and men, between migraine patients and HCs, and between female migraine patients with different hormone levels [ 6 , 29 ]. One study suggested that the FC impairments of the ACC were significantly correlated with pain severity, and pain-associated emotional disorders in menstrual migraine patients and, therefore, the ACC might be an important biomarker to differentiate migraines from HCs [ 30 ]. Additional research explored the difference in amplitude of low-frequency fluctuations and regional homogeneity between pure menstrual migraine and menstrually related migraine in the dorsolateral prefrontal cortex and medial prefrontal cortex [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occipital cortex involvement in particular can explain the plethora of visual symptoms associated with migraine, from light sensitivity to visual aura and visual snow [ 97 ]. Menstrual migraine has recently been linked to structural and functional connectivity changes in the right anterior cingulum [ 98 ] an area involved in the cognitive processing of pain and previously associated with migraine biology [ 99 ]. However, evidence from neuroimaging studies has been inconclusive at times [ 100 ], with meta-regression analyses failing to pinpoint alterations that are specific to migraine [ 101 ], showing that further research on the topic is needed.…”
Section: Migraine: Functional Anatomy and Pathophysiologymentioning
confidence: 99%